1998
DOI: 10.1137/s0097539795285771
|View full text |Cite
|
Sign up to set email alerts
|

A Spectral Algorithm for Seriation and the Consecutive Ones Problem

Abstract: Abstract. In applications ranging from DNA sequencing through archeological dating to sparse matrix reordering, a recurrent problem is the sequencing of elements in such a way that highly correlated pairs of elements are near each other. That is, given a correlation function f reflecting the desire for each pair of elements to be near each other, find all permutations π with the property that ifThis seriation problem is a generalization of the well-studied consecutive ones problem. We present a spectral algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
268
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(270 citation statements)
references
References 28 publications
1
268
0
1
Order By: Relevance
“…A heuristic algorithm for the Gap0 problem is suggested by Greenberg and Istrail [14]. They experiment with the so-called spectral algorithm initially developed for the C1P problem in [3], evaluating its performance mainly in biological terms in the context of genome reconstruction without assessing the quality of heuristic solutions from the combinatorial optimisation point of view.…”
Section: Introductionmentioning
confidence: 99%
“…A heuristic algorithm for the Gap0 problem is suggested by Greenberg and Istrail [14]. They experiment with the so-called spectral algorithm initially developed for the C1P problem in [3], evaluating its performance mainly in biological terms in the context of genome reconstruction without assessing the quality of heuristic solutions from the combinatorial optimisation point of view.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently a graph-spectral solution has been found to the problem. Atkins et al [14] have shown how to use the Fiedler eigenvector of the Laplacian matrix to sequence relational data. The method has been successfully applied to the consecutive ones problem and a number of DNA sequencing tasks.…”
Section: Introductionmentioning
confidence: 99%
“…The aim is to recover the integration path that maximises the sum of weights across the field of surface normals. This can be viewed as the problem of ordering the set of nodes in a graph in a sequence such that strongly correlated elements are placed next to one another, and this is often referred to as graph-seriation [24]. The seriation problem can be approached in a number of ways.…”
Section: B Contributionmentioning
confidence: 99%
“…However, recently a graph-spectral solution has been found to the problem. Atkins, Boman and Hendrikson [24] have shown how to use the leading eigenvector of the Laplacian matrix to sequence relational data. The method has been successfully applied to the consecutive ones problem and a number of DNA sequencing tasks.…”
Section: B Contributionmentioning
confidence: 99%
See 1 more Smart Citation